Analysis of Atmospheric Dynamics and Sea Surface Temperature as Potential Indicators of Rainfall Occurrence in West Kalimantan Province during 2022–2023 - Nadia Fithriana; Wirastuti Widyatmanti; Emilya Nurjani (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2026)
West Kalimantan Province, crossed by the equator, has a tropical climate characterized by almost year-round rainfall and relatively high average air temperatures. This condition is also accompanied by the emergence of numerous hotspots. These two climate characteristics appear contradictory, likely related to rainfall distribution patterns in the region. The purpose of this study is to analyze rainfall potential in West Kalimantan Province based on atmospheric and ocean dynamics. The data used include satellite imagery and reanalysis of each parameter: sea level pressure, wind, sea surface temperature, and altitude in 2022-2023. The analysis method is applied descriptively through plot interpretation to illustrate the data distribution and the relationships between parameters. Rainfall distribution in West Kalimantan Province is influenced by global climate dynamics and topographic conditions. In 2022, with La Nina and the southwest monsoon, rainfall was high and evenly distributed, while in 2023, with El Nino and the east monsoon, rainfall decreased, especially on the coast. The mountainous areas still receive rainfall throughout the year, although the intensity is reduced.